AB0398 COMPARATIVE SAFETY OF ABATACEPT AND OTHER NON-TUMOR NECROSIS FACTOR INHIBITORS IN RHEUMATOID ARTHRITIS: A SYSTEMATIC LITERATURE REVIEW AND NETWORK META-ANALYSIS. (June 2019) - Paul, Damemarie; Taylor, Benjamin; Kuang, Yuting; Fazeli, Mir Sohail
Abstract : Background: Abatacept has shown equivalent efficacy with other targeted therapies in rheumatoid arthritis (RA) patients 1, and equivalent or, in some cases, superior safety compared with tumor necrosis factor inhibitors (TNFi) 2, 3 . However, there is limited evidence of its safety profile relative to other non-TNFi. Objectives: To evaluate the class-level safety profile of abatacept compared with other non-TNFi in adults with moderate-to-severe RA in phase 3 and 4 clinical trials. Methods: A systematic literature review (SLR) of phase 3 and 4 randomized controlled trials (RCTs) of adults with RA was conducted. The non-TNFi included were abatacept, tocilizumab, sarilumab, tofacitinib, baricitinib and rituximab. A search from database inception until Febuary 2018 was performed on MEDLINE®, Embase, CENTRAL, and the US and EU clinical trials registries. Conference proceedings from ACR and EULAR from 2015 to end of 2017 were also reviewed. Patients who were cDMARD-naive or not receiving concommitant cDMARD treatment were excluded from the main analysis. In Bayesian network meta-analysis (NMA) random effects model, drug class-level comparisons were made with respect to the risk of total aggregated adverse events (AEs), serious AEs (SAEs), treatment-related AEs, infection, serious infection, and cancer. Results: We identified 39 RCTs that met the eligibility criteria for this SLR. The risk of bias was found to be low as assessed by the Cochrane Collaboration's tool for assessing risk of bias in randomized trials. Eight studies investigated abatacept (T-cell inhibitor), with no head-to-head comparison to other non-TNFi. Other interventions evaluated were IL-6 inhibitors (tocilizumab, n=13; sarilumab, n=3), JAK inhibitors (tofacitinib, n=7; baricitinib, n=4), and B-cell depleting agent (rituximab, n=4). The pooled study population of 27, 215 moderate-to-severe RA patients primarily consisted of middle-aged Caucasian females (mean age: 47-55 yrs;% Caucasian: 44% - 97%;% female: 69% - 88%). Thirty three trials were on patients previously treated with cDMARD or TNFi, while 6 trials were on cDMARD-naive patients. Total aggregated AEs (total AEs, n=37; SAEs, n = 37; treatment-related AEs, n = 14) and infection (serious infection, n = 35; total infection, n = 26) were the most frequently reported safety outcomes. The NMA was performed on 23 trials. Indirect comparisons were made between IL-6 inhibitors, JAK inhibitors, B cell depleting agent and abatacept, with TNFi or cDMARD as direct comparators. The risk of total AEs was significantly higher for IL-6 inhibitors compared with abatacept (RR = 1.13, 95% CrI = 1.05 – 1.22). For SAEs and other analyzed safety outcomes, no significant difference was observed between abatacept and other non-TNFi drug classes. Similar results were observed in sensitivity analyses for all patients on concomitant cDMARD, including those who were treatment-naive before the study (n=26 trials). Conclusion: When comparing aggregated safety outcomes, abatacept shared a similar safety profile with most non-TNFi RA treatments. However, patients on abatacept had a statistically significantly lower risk of total AEs compared to US recommended doses of IL-6 inhibitors. More studies with head-to-head comparison in clinical trials and real-world setting are required to provide further understanding of the safety profile and risk of specific adverse events for non-TNFi in order to optimize treatments for moderate-to-severe RA patients. References: [1] Schoels M, et al. Ann Rheum Dis2012;71(8):1303-1308 [2] Christensen R, et al. Int J Clin Rheumatol2013; 8(6):647-655 [3] Jin Y, et al. J Rheumatol2018; 45(9): 1240-1248 Disclosure of Interests: Damemarie Paul Shareholder of: Bristol-Myers Squibb, Employee of: Damemarie Paul is an employee of Bristol-Myers Squibb., Benjamin Taylor Grant/research support from: Benjamin Taylor is an employee of Doctor Evidence LLC, and the study was funded by Bristol-Myers Squibb., Yuting Kuang Grant/research support from: Yuting Kuang is an employee of Doctor Evidence LLC, and the study was funded by Bristol-Myers Squibb., Mir Sohail Fazeli Grant/research support from: Mir Sohail Fazeli is an employee of Doctor Evidence LLC, and the study was funded by Bristol-Myers Squibb.